Elementy filozofii cynickiej w edukacji szkolnej w okresie późnego Cesarstwa Rzymskiego= Elements of Cynic philosophy in primary education during the era of the late Roman Empire - Szoka, Andrzej Iwo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ancient Cynicism was a philosophy practiced up to the 4 th century A.D. Among the key sources that describe the activities of Cynics during this period are two speeches by the Roman emperor, Julian (361-363). Within these two speeches he criticized the contemporary supporters of Cynicism. Julian had an extensive knowledge about the rules of Cynicism and about the lives of its founders: Antisthenes, Diogenes of Sinope, and Crates of Thebes. He possibly acquired this knowledge during his philosophical studies.
Keywords: filozofia grecka; cynicy; edukacja grecka; retoryka - historia; Cesarstwo Rzymskie; anegdota; Cynics; Roman Empire; Greek education; Ancient rhetoric; anecdotes